Role of Blockchain Technology in Enhancing Transparency in Supply Chains - Pravin Shegade, (Journal of Computational Analysis and Applications (JoCAAA), 2024)
Supply chains have grown so long, so global, and so fragmented that no single participant cansee the whole of them, and this opacity breeds real problems: counterfeit goods slip in, ethicaland environmental claims cannot be verified, recalls are slow and imprecise, and trust between partners is expensive to maintain. Blockchain technology